Pendidikan Politik: Upaya Komisi Pemilihan Umum Sleman dalam Mewujudkan Kesadaran Politik Waria - Muhamad Iqbal Muttaqin; Ridho Al-Hamdi (Universitas Medan Area, 2023)
This article aims to measure the efforts of the General Election Commission (KPU) of Sleman Regency in providing transgender political education. The problem is focused on the lack of transgender political awareness so the KPU of Sleman Regency has an important role there. In order to approach this problem, a theoretical reference from Suryanef regarding the model of beginner voter education by democracy volunteers is used. The data were collected through qualitative methods and case study approaches, with data collection techniques in the form of interviews and literature studies and data analysis techniques using Nvivo 12 Plus. This study concludes that: (1) The voter education strategy of the KPU reaches out by researching several transgender groups through specific approaches ranging from opening communication to discussing the issue of when to implement their political education; (2) the political education materials, in general, of the KPU raise material on the function of elections, the system of electoral stages, and how to be a smart voter in exercising their right to vote when voting takes place; and (3) The political education methods provided are packaged in a variety of non-formal ways, namely in the form of seminars, lectures, visits, and interactive discussions. The obstacle felt by the Sleman Regency KPU is that there is no clear SOP for implementing political education because it is still conditional or has not been properly programmed. So this is a big challenge for them in realizing the consistency or sustainability of transgender political education in the future.